2020
DOI: 10.1111/prd.12331
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of periodontal disease pathogenesis and targets for host‐modulation therapy

Abstract: Recent advances indicate that periodontitis is driven by reciprocally reinforced interactions between a dysbiotic microbiome and dysregulated inflammation. Inflammation is not only a consequence of dysbiosis but, via mediating tissue dysfunction and damage, fuels further growth of selectively dysbiotic communities of bacteria (inflammophiles), thereby generating a self‐sustained feed‐forward loop that perpetuates the disease. These considerations provide a strong rationale for developing adjunctive host‐modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
203
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(212 citation statements)
references
References 274 publications
(400 reference statements)
2
203
0
7
Order By: Relevance
“…Interestingly, the effect of F. nucleatum on the SOD2 and BIRC3 levels was similar to the actions of clinical periodontal infection, confirming the important etiological role of F. nucleatum in periodontitis. However, periodontitis is caused by a complex multispecies biofilm [ 8 ]. Future in-vitro studies on the interactions between microbial and mechanical signals should also include living complex biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effect of F. nucleatum on the SOD2 and BIRC3 levels was similar to the actions of clinical periodontal infection, confirming the important etiological role of F. nucleatum in periodontitis. However, periodontitis is caused by a complex multispecies biofilm [ 8 ]. Future in-vitro studies on the interactions between microbial and mechanical signals should also include living complex biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontopathogenic bacteria induce inflammatory cells to produce a wide range of proinflammatory mediators, proteases, and osteoclast-activating factors, which can mediate or directly cause destruction of periodontal tissues and structures [ 7 , 8 ]. Animal experiments have provided evidence that occlusal overloading can aggravate periodontal diseases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…During periodontitis, the severe form of periodontal disease, inflammatory cells recruited in response to the bacterial challenge secrete a broad array of inflammatory mediators that mediate the destruction of both soft and hard tissue [ 6 ]. Given the key role played by the bacteria-mediated immuno-inflammatory process in the progression and severity of periodontitis, modulating this host inflammatory response may constitute a potential therapeutic strategy [ 11 , 12 ]. Host modulation can be defined as a therapeutic approach aimed at restoring the balance between proinflammatory and anti-inflammatory mediators to stop the progression of the disease and to create an environment favorable to inflammation resolution and tissue repair [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, which originate either from circulating monocytes or from embryo-derived precursors, are found in higher numbers in active periodontal lesions than in inactive sites [ 9 ]. The continuous excessive secretion of various cytokines and matrix metalloproteinases (MMPs) by macrophages following the recognition of periodontal bacteria by the toll-like receptor pathway modulates periodontal tissue destruction [ 1 , 10 , 11 ]. Active compounds endowed with a capacity to down-regulate the inflammatory response of macrophages may thus be regarded as potential new therapeutic agents for the treatment of periodontal diseases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease is a chronic inflammatory disease of tooth-supporting tissues, primarily caused by periodontopathic bacterial infection [ 1 , 2 ]. In the progressive form of the disease, extensive loss of tooth-supporting tissues can be found, and diseased teeth are extracted due to their considerable mobility [ 3 ]. In addition to the negative effects on masticatory function, recent studies have suggested that the chronic inflammation of periodontal tissues may contribute toward several systemic diseases, including diabetes and cardiovascular disease, and have emphasized the importance of periodontal treatment in terms of systemic health [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%